On the intersection of two subgeometries of PG(n, q) - Donati, Giorgio; Durante, Nicola (Designs, codes, and cryptography, 2008)
The study of the intersection of two Baer subgeometries of PG ( n , q ), q a square, started in Bose et al. (Utilitas Math 17 , 65–77, 1980); Bruen (Arch Math 39 (3), 285–288, (1982). Later, in Svéd (Baer subspaces in the n-dimensional projective space. Springer-Verlag) and Jagos et al. (Acta Sci Math 69 (1–2), 419–429, 2003), the structure of the intersection of two Baer subgeometries of PG ( n , q ) has been completely determined. In this paper, generalizing the previous results, we determine all possible intersection configurations of any two subgeometries of PG ( n , q ).